Return of Stored Goods; Comparative Analysis of the Laws between the Shafi'i and the Hanafi School - Hazrazil; Lewa, Irfan (Universitas Islam Negeri Alauddin Makassar, 2021)
This article discusses the punishment for thieves who return stolen goods from the perspective of the Syafi’i school and the Hanafi school. The type of research used by the author in completing this research is qualitative research which is a type of literature research conducted by finding and reviewing written sources such as books and so on. This research uses a juridical normative approach, which is the approach used in relation to the core issues obtained by various sources of literature both primary and secondary or based on the Qur'an, sunnah and consensus of scholars. The results of this study have shown that there are differences and similarities of opinion between the Syafi'I school and the Hanafi school with their respective methods of legal inference. Based on the opinion of the Syafi'i school that if a thief takes the property of another person then the thief gives back the property in a state known to the owner of the goods or not known at all and has been reported to the authorities or not reported then the thief will not escape punishment because it has exceeded two rights, namely the rights of God and human rights. The right of God in question is to violate the command or decree that has been established by God Almighty that stealing is forbidden, and the human right that is violated is to take property that is not his at all. Whereas the Hanafi sect of thieves will not be subject to a limit penalty if the perpetrator returns in circumstances not yet known to the owner and either has been reported or not to the judge. The thief is sentenced to a limit if he returns it after the owner knows because it can cause anger that leads to a limit penalty